DIAGNOSIS OF ENDOCRINE DISEASE: The diagnostic performance of adrenal biopsy: a systematic review and meta-analysis. Issue 2 (August 2016) - Bancos, Irina; Tamhane, Shrikant; Shah, Muhammad; Delivanis, Danae A; Alahdab, Fares; Arlt, Wiebke; Fassnacht, Martin; Murad, M Hassan
Abstract : Objective: To perform a systematic review of published literature on adrenal biopsy and to assess its performance in diagnosing adrenal malignancy. Methods: Medline In-Process and Other Non-Indexed Citations, MEDLINE, EMBASE, and Cochrane Central Register of Controlled Trial were searched from inception to February 2016. Reviewers extracted data and assessed methodological quality in duplicate. Results: We included 32 observational studies reporting on 2174 patients (39.4% women, mean age 59.8 years) undergoing 2190 adrenal mass biopsy procedures. Pathology was described in 1621/2190 adrenal lesions (689 metastases, 68 adrenocortical carcinomas, 64 other malignancies, 464 adenomas, 226 other benign, 36 pheochromocytomas, and 74 others). The pooled non-diagnostic rate (30 studies, 2013 adrenal biopsies) was 8.7% (95%CI: 6–11%). The pooled complication rate (25 studies, 1339 biopsies) was 2.5% (95%CI: 1.5–3.4%). Studies were at a moderate risk for bias. Most limitations related to patient selection, assessment of outcome, and adequacy of follow-up. Only eight studies (240 patients) could be included in the diagnostic performance analysis with a sensitivity and specificity of 87 and 100% for malignancy, 70 and 98% for adrenocortical carcinoma, and 87 and 96% for metastasis respectively. Conclusions: Evidence based on small sample size and moderate risk of bias suggests that adrenal biopsy appears to be most useful in the diagnosis of adrenal metastasis in patients with a history of extra-adrenal malignancy. Adrenal biopsy should only be performed if the expected findings are likely to alter the management of the individual patient and after biochemical exclusion of catecholamine-producing tumors to help prevent potentially life-threatening complications.